Tissue engineered constructs based on SPCL scaffolds cultured with goat marrow cells : functionality in femoral defects - Rodrigues, Márcia T. (2011)
This study aims to assess the in vivo performance of cell–scaffold constructs composed of goat marrow stromal cells (GBMCs) and SPCL (a blend of starch with polycaprolactone) fibre mesh scaffolds at different stages of development, using an autologous model. GBMCs from iliac crests were seeded onto SPCL scaffolds and in vitro cultured for 1 and 7 days in osteogenic medium. After 1 and 7 days, the constructs were characterized for proliferation and initial osteoblastic expression by alkaline phosphatase (ALP) activity. Scanning electron microscopy analysis was performed to investigate cellularmorphology and adhesion to SPCL scaffolds. Non-critical defects (diameter 6 mm, depth 3 mm) were drilled in the posterior femurs of four adult goats from which bone marrow and serum had been collected previously. Drill defects alone and defects filled with scaffolds without cells were used as controls. After implantation, intravital fluorescence markers, xylenol orange, calcein green and tetracycline, were injected subcutaneously after 2, 4 and 6 weeks, respectively, for bone formation and mineralization monitoring. Subsequently, samples were stained with L´evai–Laczk´o for bone formation and histomorphometric analysis. GBMCs adhered and proliferated on SPCL scaffolds and an initial differentiation into pre-osteoblasts was detected by an increasing level of ALP activity with the culture time. In vivo experiments indicated that bone neoformation occurred in all femoral defects. The results obtained provided important information about the performance of SPCL–GBMC constructs in an orthotopic goat model that enabled future studies to be designed to investigate in vivo the functionality of SPCL–GBMC constructs in more complex models, viz. critical sized defects, and to evaluate the influence of in vitro cultured autologous cells in the healing and bone regenerative process.